2017
DOI: 10.1111/zsc.12235
|View full text |Cite
|
Sign up to set email alerts
|

Museum archives revisited: Central Asiatic hawkmoths reveal exceptionally high late Pliocene species diversification (Lepidoptera, Sphingidae)

Abstract: Three high‐elevation Hyles species of Central Asia have proven difficult to sample, and thus, only a limited number of specimens are available for study. Ancient DNA techniques were applied to sequence two mitochondrial genes from ‘historic’ museum specimens of Hyles gallii, Hyles renneri and Hyles salangensis to elucidate the phylogenetic relationships of these species. This approach enabled us to include the holotypes and paratypes. The status of H. salangensis as a species endemic to a mountain range north … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
(142 reference statements)
1
17
0
Order By: Relevance
“…Ongoing developments with DNA sequencing technologies are enabling researchers to tap into genetic data that were previously inaccessible (Cooper 1994;Lan & Lindqvist 2019). Incorporating genetic data from natural history collections representing rare/threatened species and species that are otherwise hard to access into genetic-based analyses can provide critical insights (Heckeberg et al 2016;Hundsdoerfer et al 2017;McGuire et al 2018). For example, genetic data from museum specimens has been used to track temporal and spatial changes in species distributions (Lozier & Cameron 2009), investigate population genetics (Spurgin et al 2014;Schmid et al 2018), and evaluate conservation implications (Anco et al 2018;Brandt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing developments with DNA sequencing technologies are enabling researchers to tap into genetic data that were previously inaccessible (Cooper 1994;Lan & Lindqvist 2019). Incorporating genetic data from natural history collections representing rare/threatened species and species that are otherwise hard to access into genetic-based analyses can provide critical insights (Heckeberg et al 2016;Hundsdoerfer et al 2017;McGuire et al 2018). For example, genetic data from museum specimens has been used to track temporal and spatial changes in species distributions (Lozier & Cameron 2009), investigate population genetics (Spurgin et al 2014;Schmid et al 2018), and evaluate conservation implications (Anco et al 2018;Brandt et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although feeding on Nyctaginaceae by larvae of H. annei was already recorded (Butler 1882;Moss 1912), this is the first confirmed record of A. incarnata as a host of this hawkmoth. Species of Zygophyllaceae have been recorded as host plants of three species of Hyles Hübner, (1819) (Robinson et al 2010;Hundsdoerfer et al 2017); however, this is the first confirmed record of a representative of the Zygophyllaceae as a host plant of H. annei. As A. incarnata is distributed from the United States to Argentina and Chile (Turner 1994), it could be used by H. annei throughout its range.…”
Section: Observationsmentioning
confidence: 96%
“…The Neotropical hawkmoth, Hyles annei (Guérin-Méneville, 1839) (Lepidoptera: Sphingidae: Macroglossinae: Macroglossini), is known from Argentina, Bolivia, Chile and Peru (Ureta and Donoso 1956;Haxaire and Herbin 1999;Cock and Boos 2006;Moré et al 2014), where it has been found in a wide range of habitats from sea level to more than 2000 m elevation (Hundsdoerfer et al 2009;Juárez and González 2016). It is a polyphagous species (Hundsdoerfer et al 2017); however, its native host plant range has not been studied in detail in most of its geographic distribution. In Chile, Butler (1882) recorded "Oxybaptrus parviflorus", probably involving one of the eight species of Mirabilis Riv.…”
Section: Introductionmentioning
confidence: 99%
“…DNA concentration of old samples was measured with a NanoDropOne spectrophotometer. We followed a workflow previously used by other authors (Hebert et al 2013, Mitchell 2015, Hundsdoerfer et al 2017) by amplifying up to five short overlapping fragments covering the COI barcode part (see Suppl. material 1: Fig.…”
Section: Molecular Workmentioning
confidence: 99%